The animated pocket dictionary of hypertension - Focus Medica ([Singapore] : Focus Medica, 2011)
The FOCUS Animated Pocket Dictionary of Hypertension, the first ever animated dictionary in the subject, is a comprehensive reference source for the definition of terms related to hypertension. A must-have resource for physicians and students who would greatly benefit from this module, it covers related terms and definitions. All the definitions have been graphically described with breathtaking, state of the art 3D animations.
A-W.
System requirements: DVD-ROM drive; OS Windows 98/ME/XP/Windows vista, CPU PIII/1Ghz; RAM 128Mb preferred.
Keywords: Hypertension; Dictionary; Electronic books